Billy Sunday, home run to heaven - Allen, Robert A.; Shaw, Charles, 1941-2005 (Milford, Mich. : Mott Media, 1985)
A biography of a professional baseball player who dedicated his life to spreading the gospel and became one of the most influential religious figures of the early twentieth century.
Includes bibliographical references (pages 149-150).
Keywords: Sunday, Billy, -- 1862-1935 -- Juvenile literature; Sunday, Billy, -- 1862-1935.; Sunday, Billy, -- 1862-1935.; Evangelists -- United States -- Biography -- Juvenile literature; Baseball players -- United States -- Biography -- Juvenile literature; Evangelists; Baseball players; Christian biography; Baseball players; Evangelists; United States; Literature; Biographies; Biography; Juvenile works; Biographies; Literature